(untitled) (Journal of Economic Research & Business Administration, 2016)
In a word human progress there is a difference in life-span, literacy, education and earnings of men and women, here possibilities of men. The consequences of transitional period strengthened gender inequity in the political. One of important factors of increase of employment among women in our country is development of small business. They provide the population of the country and the market with need goods of a household purpose are sources of increase of a standard of living of the population by means of economic independence are also instruments of formation of individual enterprise abilities. Vocational guidance of female business is usually tradi-tional; it is generally light industry, public catering, consulting and educa-tional services, traditional medicine, and cosmetology services.